A Clinical Nomogram for Predicting Lymph Node Metastasis in Penile Cancer: A SEER-Based Study - Zhang, Wei; Gao, Pan; Gao, Jingjing; Wu, Xu; Liu, Guodong; Zhang, Xiansheng (Frontiers in Oncology, 2021)
Abstract Purpose: We developed a nomogram to predict the possibility of lymph node metastasis in patients with squamous cell carcinoma of the penis. Methods: Identifying patients with squamous cell carcinoma of the penis diagnosed between 2004 and 2015 in the Surveillance, Epidemiology, and End Results (SEER) database. Univariate and multivariate analyses were carried out by logistic regression to assess significant predictors associated with lymph node metastasis. A nomogram was established and validated by a calibration plot and receptor operating characteristic curve (ROC) analysis. Results: A total of 1016 patients with penile squamous cell carcinoma (SCCP) were enrolled in this study. 195 patients (19%) had lymph node involvement (N1-3). Multivariate analysis showed that age, primary tumor site, grade, tumor size, and T stage were identified as being significantly (p < 0.05) associated with lymph node involvement. All the above factors that showed a statistically significant predictive capability were selected for building the nomogram. This model had a calibration slope of 0.9 and a c-index of 0.776, indicating the good discrimination and effectiveness of the nomogram in predicting lymph node status. Conclusion: Although the prediction model has some limitations, the nomogram revealed the relationship between the clinicopathological characteristics of SCCP patients and the risk of lymph node metastasis. This tool will assist patients in counseling and guide treatment decisions for SCCP patients.